MAYA ANGELOU’S USE OF AFRICAN-AMERICAN ORAL TRADITIONS IN POETRY - Chandrashekharappa S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Maya Angelou’s poetry is deeply rooted in African-American oral traditions, drawing from the rhythmic structures, storytelling techniques, and performative aspects of Black cultural expression. Her work reflects the historical and cultural continuity of African oral traditions, which have been preserved and adapted by African Americans through spirituals, work songs, blues, jazz, and spoken-word performance. By incorporating these elements into her poetry, Angelou creates a literary experience that transcends the written word, embodying the communal, interactive, and expressive nature of oral storytelling. A key feature of Angelou’s poetry is her use of rhythm and repetition, mirroring the call-and-response patterns found in African-American spirituals and gospel music. This technique enhances engagement and reinforces central themes of resilience, empowerment, and survival. Her frequent use of vernacular language and dialect also reflects the oral tradition’s emphasis on authenticity and accessibility, making her poetry resonate with a broad audience. Additionally, Angelou employs lyrical qualities derived from blues and jazz, incorporating musicality and improvisation into her verses to evoke deep emotional responses. Angelou’s poetry also functions as a continuation of African-American storytelling traditions, blending autobiography with collective history. Her narrative-driven poems often serve as parables, carrying moral and ethical lessons similar to the griot storytelling tradition in West Africa. Moreover, she draws upon African ritualistic and spiritual elements, using poetic incantations and affirmations that parallel the structure of Black church sermons. Another significant aspect of her work is its function as a tool of protest and resistance, much like the oral traditions of enslaved Africans and the Civil Rights Movement. Her use of metaphor, symbolism, and signifying techniques critiques societal injustices while celebrating Black identity and resilience. Additionally, her poetry is inherently performative, emphasizing the power of voice and speech to transform words into a living, communal experience. Through her mastery of African-American oral traditions, Maya Angelou ensures that the voices of the past continue to shape the present and future. Her poetry serves as both a historical record and an affirmation of the enduring power of Black cultural expression.